Autoantibody of interleukin-17A induced by recombinant Mycobacterium smegmatis attenuates airway inflammation in mice with neutrophilic asthma. (3rd October 2022) - Chen, Ling; Xu, Wanting; Mao, Song; Zhu, Ruochen; Zhang, Jianhua
Abstract: Objective: Previous studies have shown Interleukin (IL)-17A as an important contributor to the development of severe asthma, which is mainly characterized by neutrophilic inflammation and less response to corticosteroids. Consequently, the IL-17A-neutrophil axis could be a potential therapeutic target. Previously, we constructed a recombinant Mycobacterium smegmatis (rMS) expressing fusion protein Ag85A-IL-17A, and confirmed it could induce production of IL-17A autoantibody in vivo . This study uses a murine model of neutrophilic asthma to further investigate the effects of rMS on airway inflammation. Methods: DO11.10 mice were divided into four groups: phosphate buffered saline (PBS), asthma, rMS and MS. This murine model of neutrophilic asthma was established with ovalbumin (OVA) challenge, whereby PBS, rMS and MS were administered intranasally. Anti-inflammatory effects on inflammatory cell infiltration and expression of inflammatory mediators in bronchoalveolar lavage fluid (BALF) were evaluated, along with histopathological changes in lung tissues. Results: A sustained high-titer IL-17A autoantibody was detected in sera of the rMS group. Compared to the asthma group, the number of neutrophils, IL-17A, CXCL-1 levels and MPO activity in the rMS group were all significantly reduced ( p < 0.01). Histological analysis showed rMS remarkably suppressed inflammatory infiltration around bronchia. The inflammation score and the mucus score in the rMS group were both significantly lower than those in the asthma group ( p < 0.001). Conclusion: rMS ameliorated airway inflammation in mice with neutrophilic asthma caused by inducing IL-17A autoantibody and regulating the IL-17A-neutrophil axis, thus offering a possible novel treatment for neutrophilic asthma.